2011
DOI: 10.1111/j.1460-9592.2011.03718.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic gastric antral area and gastric contents volume in children

Abstract: Correlations between GAA and TGV(w) or GFV(w) in children are best in the RDC position, but not sufficient to predict GFV(w) with a given GAA. Interpretation of isolated GAA values may be misleading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 18 publications
7
78
2
Order By: Relevance
“…The RLD scan position is reportedly better for estimation of gastric volume [9,10]. Even in the supine position, the correlation coefficient of our data was slightly lower than the data of the two abovementioned previous studies [9,10]. This may be due to the following reasons.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The RLD scan position is reportedly better for estimation of gastric volume [9,10]. Even in the supine position, the correlation coefficient of our data was slightly lower than the data of the two abovementioned previous studies [9,10]. This may be due to the following reasons.…”
Section: Discussioncontrasting
confidence: 81%
“…Schmitz et al showed that antral CSA was positively correlated with gastric volume; the correlation coefficients were 0.62 in the supine position and 0.73 in the RLD position in conscious healthy volunteers aged 6-12 years. Gastric volume was measured by magnetic resonance imaging [9]. However, this previous study did not include younger children, so it is likely that positioning during scanning was relatively easier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the "empty" antrum appears "flat" (the anterior and posterior walls nearly closed against each other) or round like a "bull's eye" target ( Fig 3A,B), 24 GAA was calculated using the following formula, as previously described. [18][19][20] …”
Section: Methodsmentioning
confidence: 98%
“…1). [18][19][20] Next, a high-frequency linear probe was applied to obtain images from the same point as that in the sagittal scanning plane. The image acquisitions were repeated five times between the peristaltic antral contractions to accurately measure the outcome variables.…”
Section: Methodsmentioning
confidence: 99%